2024
DOI: 10.1167/iovs.65.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris and Retinal Vascular Alterations in Presymptomatic Alzheimer's Disease

Giulia Corradetti,
Deniz Oncel,
Shin Kadomoto
et al.

Abstract: Purpose To compare optical coherence tomography angiography (OCTA) retina metrics between cognitively healthy subjects with pathological versus normal cerebrospinal fluid (CSF) Aβ 42 /tau ratios. Methods Swept-source OCTA scans were collected using the Zeiss PLEX Elite 9000 and analyzed on 23 cognitively healthy (CH) subjects who had previously undergone CSF analysis. Thirteen subjects had a pathological Aβ 42 /tau (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Moreover, a wide range of retinal microvascular and choriocapillaris changes in AD patients such as lower densities, sparser vasculature, increased tortuosity, and lower fractal dimensions have been shown in OCTA studies. 8 , 49 , 50 , 51 , 52 , 53 Here we showed that EOAD patients had lower retinal microvascular and choriocapillaris densities and sparser retinal microvascular and choriocapillaris compared to controls. These findings are in line with previous OCTA analyses.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, a wide range of retinal microvascular and choriocapillaris changes in AD patients such as lower densities, sparser vasculature, increased tortuosity, and lower fractal dimensions have been shown in OCTA studies. 8 , 49 , 50 , 51 , 52 , 53 Here we showed that EOAD patients had lower retinal microvascular and choriocapillaris densities and sparser retinal microvascular and choriocapillaris compared to controls. These findings are in line with previous OCTA analyses.…”
Section: Discussionmentioning
confidence: 49%
“…The exact mechanisms underlying this association remain unclear, but the cerebral neurodegenerative changes leading to AD may result in similar pathological changes in the retinal microvasculature. Decreased retinal circulation has been reported in studies of patients with AD 41 . Neurotoxicity due to the accumulation of amyloid-β in the retinal vasculature may also cause damage to vascular epithelial cells, leading to retinal microvascular damage 42 .…”
Section: Discussionmentioning
confidence: 81%